Exploring the personal adoption and use of generative artificial intelligence in work and decision-making by employees of multinational corporations : a technology acceptance model perspective - Van Eck, Danéel (University of Pretoria, 2025)
Mini Dissertation (MPhil (International Business))--University of Pretoria, 2024.